Circular single-stranded DNA as switchable vector for gene expression in mammalian cells - Linlin Tang; Zhijin Tian; Jin Cheng; Yijing Zhang; Yongxiu Song; Yan Liu; Jinghao Wang; Pengfei Zhang; Yonggang Ke; Friedrich C. Simmel; Jie Song (Nature Communications, 2023)
Abstract Synthetic gene networks in mammalian cells are currently limited to either protein-based transcription factors or RNA-based regulators. Here, we demonstrate a regulatory approach based on circular single-stranded DNA (Css DNA), which can be used as an efficient expression vector with switchable activity, enabling gene regulation in mammalian cells. The Css DNA is transformed into its double-stranded form via DNA replication and used as vectors encoding a variety of different proteins in a wide range of cell lines as well as in mice. The rich repository of DNA nanotechnology allows to use sort single-stranded DNA effectors to fold Css DNA into DNA nanostructures of different complexity, leading the gene expression to programmable inhibition and subsequently re-activation via toehold-mediated strand displacement. The regulatory strategy from Css DNA can thus expand the molecular toolbox for the realization of synthetic regulatory networks with potential applications in genetic diagnosis and gene therapy.